La peinture murale antique Restitution et iconographie - Barbet, Alix (Documents d'archéologie française, 1987)
This volume includes the Acts of the IXth Conference of the A.F.P.M.A. (French Antique Wall Paintings Association), one of the majorthemes of which is the graphic restitution of fragmentary paintings, tracings and colour rendering, problems which are common to other sectors of archaeology. These restitutions, which are linked to restorations, must be came out in accordance with very strict principles, which respect completely what is left of the original work. The advantages of exchanges between archaeologists and restorers are here made obvious, with reports from both professions on the same, often unpublished, paintings. The second theme concerns the iconography, as a reconstitution calls on a knowledge of the various decorative and figurative themes employed and which vary in accordance with the possible interpretations. Both archaeologists and restorers will find this publication offers food for thought in the daily details of their work.